AG POLYMORPHISM AS A CYTOGENETIC MAKER OF ARTERIAL HYPERTENSION RISK - I. N. Medvedev; I. V. Amelina (Российский кардиологический журнал, 2009)
The aim of the study was to investigate the phenotypic manifestations of chromosome nucleoli area transcription activity, at the level of erythrocyte cell membrane main proteins, as a cytogenetic marker of arterial hypertension (AH) risk. The comparison of AH patients and people at AH risk demonstrated significantly reduced activity of nucleoli area 10Ag activity, comparing to the main population. In the former, this could explain less active erythrocyte membrane protein synthesis, linked to AH development. Therefore, human nucleoli area 10Ag levels could be regarded as a cytogenetic marker of AH risk and development.